2012
DOI: 10.1002/fuce.201100126
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Analysis of SOFC Cathode Reaction Using Evolutionary Programming

Abstract: Investigation of the cathode reaction in solid oxide fuel cells (SOFC) by impedance spectroscopy (IS) measurements using evolutionary‐based programming analysis is demonstrated. In contrast to the conventional analysis methods used for impedance spectroscopy measurements, e.g., equivalent circuits, the impedance spectroscopy genetic programming (ISGP) program seeks for a distribution of relaxation times that has the form of a peak or a sum of several peaks, assuming the Debye kernel. Using this method one find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Partial identification of the features of the impedance spectra of the membranes were made previously . In the current work, ISGP was implemented because of its proven ability to distinguish between dielectric response and electrochemical response in fuel cells, batteries and super‐capacitors . The program determines the extent to which the Kramers‐Kronig (KK) relations are obeyed by the real and imaginary parts of the complex impedance data (Section S3, Supporting Information)…”
Section: Methodsmentioning
confidence: 99%
“…Partial identification of the features of the impedance spectra of the membranes were made previously . In the current work, ISGP was implemented because of its proven ability to distinguish between dielectric response and electrochemical response in fuel cells, batteries and super‐capacitors . The program determines the extent to which the Kramers‐Kronig (KK) relations are obeyed by the real and imaginary parts of the complex impedance data (Section S3, Supporting Information)…”
Section: Methodsmentioning
confidence: 99%
“…Several different ECs can result in the same spectrum, leading to completely different physical interpretations (Baltianski and Tsur 2003). Thus, other modern analysis techniques, notably Impedance Spectroscopy Genetic Programming (ISGP) (Hershkovitz et al 2011, Hershkovitz et al 2012, Drach et al 2016, Oz et al 2016, Oz et al 2017, analyzing distribution of relaxation times in the system, and mechanistic models (Amphlett et al 1995, Springer et al 1996, Franco et al 2007, Reshetenko and Kulikovsky 2017, are being also employed.…”
Section: Characterization Of Pem Transport Properties 41 In Situ Pemmentioning
confidence: 99%
“…This model is usually comprised of an additional parameter, R 0 , accounts for series resistance. Our previous work [11] have shown that series resistance results in a single peak in the DFRT outside the measured bandwidth, at high frequencies, so it will not be discussed in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…This equation is an ill-posed inverse problem which cannot be solved directly. In order to find the DFRT model that fits best the measured data we analyze it using Impedance Spectroscopy Genetic Programming (ISGP) [8][9][10][11], a novel technique to find a functional form of the DFRT using a genetic algorithm. It starts with an initial guess of models, each model comprised of a combination of one or more known mathematical peaks (e.g.…”
Section: Introductionmentioning
confidence: 99%